Evaluasi Sifat Fisik Kaplet Asam Mefenamat Generik Berlogo dan Bermerek - Ferdy Firmansyah (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2020)
Mefenamic acid is one of the drugs of choice for analgesic, anti-inflammatory and antipyretic treatments. This drug is in the form of caplets, capsules and suspensions. The community still considers that drugs with branded generic names are more qualified than generic drugs with logos. This study aims to evaluate the physical properties of branded generic mefenamic acid caplets and branded generics in the Tampan District of Pekanbaru City. Sampling was carried out from 2 generic products bearing the logo (G1 and G2) and 2 branded generic products (M1 and M2). The results of the physical properties evaluation of mefenamic acid caplets obtained were weight diversity test with percent weight in the range of 98.017-101.491%; size uniformity test which has a thickness in the range of 0.440-0.545 cm and a diameter range of 0.682-0.828 cm; hardness test has a range of 8.8-11.1 kg/cm2; fragility test with a range of 0.024-0.316%; endurance test ranges from 0.008 to 0.200%; and disintegration time test which ranges from 3 minutes 58 seconds to 19 minutes 55 seconds. Based on the results of this study it can be concluded that the evaluation of the physical properties of generic mefenamic acid caplets with branded and generic branded brands has fulfilled the physical properties requirements listed in the Indonesian Pharmacopoeia Edition IV and V.